2008
DOI: 10.3920/wmj2008.x005
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative detection of Fusarium spp. and its correlation with fumonisin content in maize from South African subsistence farmers

Abstract: A quantitative detection tool was developed to enable the monitoring of fumonisin-producing fungi in food and feed commodities. To this end, a quantitative PCR (TaqMan) was developed that targets a conserved region in the polyketide synthase gene fum1, which is involved in the biosynthesis of fumonisin. Hence, this method specifically detected isolates from the fumonisin-producing species Fusarium verticillioides, F. proliferatum, F. nygamai and F. globosum whereas isolates of the fumonisin non-producing speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 34 publications
1
33
0
Order By: Relevance
“…TaqMan reactions were performed in 25 µl, using 12.5 µl of TaqMan universal PCR master mix (Applied Biosystems) and 100 nM of FAM-labeled target and internal control probe and 400 nM of forward and reverse primer for both the target F. graminearum (Waalwijk et al 2004(Waalwijk et al , 2008 as well as the internal positive control (Klerks et al 2004). TaqMan reactions were performed on 2 µl of DNA preparations from samples.…”
Section: Determination Of F Graminearum Dna Content On Wheat Grain Amentioning
confidence: 99%
“…TaqMan reactions were performed in 25 µl, using 12.5 µl of TaqMan universal PCR master mix (Applied Biosystems) and 100 nM of FAM-labeled target and internal control probe and 400 nM of forward and reverse primer for both the target F. graminearum (Waalwijk et al 2004(Waalwijk et al , 2008 as well as the internal positive control (Klerks et al 2004). TaqMan reactions were performed on 2 µl of DNA preparations from samples.…”
Section: Determination Of F Graminearum Dna Content On Wheat Grain Amentioning
confidence: 99%
“…that produce fumonisins using primers and probes designed for the polyketide synthase gene fum1. 24 qPCR was performed using a MicroAmp Optical 96-well reaction plate and MicroAmp Optical Caps (Applied Biosystems, Foster City, USA). An ABI Prism 7700 Sequence Detection System (Applied Biosystems) was used to perform the PCR and assess fluorescence.…”
mentioning
confidence: 99%
“…In Eastern and Southern Africa fumonisin B 1 was detected at concentrations ranging from 0.002 to 1.91 mg kg -1 (92.5% positive samples), while the sum of fumonisin (B 1 + B 2 + B 3 ) concentrations in the same samples ranged from 0.002 to 2.73 mg kg -1 . The results of frequent fumonisin occurrence at a high level combined with very high maize intake indicated that FB s levels in maize from Africa regularly exceed the tolerable daily intake for fumonisins (Waalwijk et al 2008). These are alarming quantities in particular taking into account the maximum recommended levels of this toxin according to the guidance values.…”
Section: Discussionmentioning
confidence: 99%